Asociación entre la temática de tesis de pregrado y su publicación en revistas científicas indizadas, en una universidad privada de Lima, Perú - Rojas-Castro, Valeria Alexandra (2025)
Introduction: Scientific research is key in academic training and knowledge development. As a requirement for obtaining a professional degree, undergraduate students must present a thesis, of which only a small percentage is published in indexed scientific journals. Objective: To evaluate the association between the topic of undergraduate theses in the field of human medicine in Lima, Peru, and publication in indexed scientific journals. Materials and methods: Observational, analytical, and longitudinal study based on undergraduate theses from the Faculty of Human Medicine at a private university in Lima. Undergraduate theses were included from the period 2004–2023, excluding those from graduate programs. The sampling was non-probabilistic, census type. The dependent variable was publication in indexed journals, and the independent variable was thesis topic. Poisson regression was used to determine the association. Results: Of the 431 theses analyzed, the most common topic and design were clinical (57.5%) and observational (81.6%), respectively. Of the total, 29% (n=125) were published in scientific journals, of which 81.6% (n=102) were indexed in SCOPUS. The h-index value of the advisor, both in SCOPUS and Google Scholar, showed significantly higher values for the published theses compared to those that were not published. Finally, in the adjusted analysis, epidemiology and public health topics had a 1.4 times higher probability of being published compared to clinical topics. Conclusion: There is a significant relationship between the thesis topic in Peru and publication in indexed scientific journals.